Selective laser sintering of distinct drug and polymer layers as a novel manufacturing strategy for individually dosed tablets - Jonas Autenrieth; Daniel Hedbom; Maria Strømme; Thomas Kipping; Jonas Lindh; Julian Quodbach (International Journal of Pharmaceutics: X)
Selective Laser Sintering (SLS) is an emerging additive manufacturing technology with potential for the production of personalized pharmaceuticals. In this study, we investigated a novel simplified formulation approach in SLS-based manufacturing of individually dosed, multi-layered tablets with distinct layers of pure active pharmaceutical ingredient (API) and excipient. Indomethacin (IND) was chosen as the model API, and polyvinyl alcohol (PVA) served as the excipient. Unlike conventional methods requiring powder blending, this approach utilizes separate powder tanks for IND and PVA, enabling direct printing of alternating layers in a single-step procedure.We successfully fabricated tablets with controlled IND doses by varying the number of IND layers, maintaining consistent printing parameters across different compositions and confirming the API's chemical stability in the product. Since SLS is conventionally used for thermoplastic substances, the successful sintering of pure IND layers was a key achievement in the study, as this crystalline API is typically not printable separately. Energy dispersive X-ray spectroscopy (EDS) demonstrated the successful formation of distinct API and excipient layers. Differential scanning calorimetry (DSC) characterization revealed that the sintering process partially amorphized IND, which may enhance dissolution and bioavailability. Dissolution testing indicated that the printed tablets exhibited improved dissolution rates compared to raw IND powder.The study successfully demonstrated the possibility of SLS-based production for personalized dosing by omitting powder blending steps. The ability to create individualized dosages with minimal excipients and simplified processing represents a step toward further investigation of SLS for clinical settings, including hospital and pharmacy-based drug production.